Profitability, Earnings Per Share on Stock Return with Size as Moderation - Jumawan Jasman; Muhammad Kasran (TRIKONOMIKA, 2017)
The purpose of this study was to analyze the effect of profitability and earnings per share on stock returns and the role of size as a moderating variable in state-owned companies listed in the Indonesia Stock Exchange (IDX) in the period of 2011-2016. By using purposive sampling, the number of samples included 18 companies. Method was conducted by downloading summary of financial statements in the Indonesia Stock Exchange. The research began with classical assumption test, multiple linear regression analysis was done with the absolute difference test. The research found that profitability had no effect on stock return. Earnings per share and size had a significant negative effect on stock return. The role of size as a moderating variable strengthened the relationship of earnings per share with stock returns, but it did not play a role in the relationship of profitability with stock returns.